Cardinal Bessarion (1403-1472) most Latin of Greeks, most Greek of Latins - Malone-Lee, Michael (Routledge, Taylor & Francis Group, 2024)
"Cardinal Bessarion was a towering figure in the fifteenth century Renaissance. His life spanned the century. In his sixty-nine years of life he was a stellar student, a Basilian monk, a Greek Orthodox archbishop, a Roman cardinal, a papal diplomat, an eminent humanist and scholar. Bessarion's life and career were shaped by the tidal wave of the advance of the Ottoman Turks towards the West, and by the centuries' old tension between the Orthodox East and the Latin West. He made a significant impact in both these areas. His long-term legacy is his contribution to the revival of classical learning in the revival of classical learning in the Renaissance. This biography presents the life of Cardinal Bessarion, exploring his personal perspective on his age and his experience. It will be of interest to anybody with an interest in the European Renaissance and to specialists in Christian/Islamic relations in the period, the theological tensions between the Latin West and the Greek East, and the history of scholarship"--
Keywords: Bessarion -- Kardinal -- 1408-1472; Bēssariōn / Cardinal / 1403-1472; Cardinals / Italy / Biography; Humanists / Italy / Biography; Church history / Middle Ages, 600-1500; Cardinaux / Italie / Biographies; Humanistes / Italie / Biographies; Église / Histoire / 600-1500 (Moyen Âge); Cardinals; Church history / Middle Ages; Humanists; Italy; 600-1500; Biographies; Biografie